Purchasing strategy to minimize financial losses for customer support division on aerospace industry company - Gemma Grimaldi; Gatot Yudoko (Faculty of Economics and Business Mulawarman University, 2018)
The Customer Support at an aerospace industry company, is on division who handles after sales support to customers. The workload keeps getting bigger everyday due to the requirements of the customers to keep their aircraft at serviceable condition. They are facing big issues due to high number of Customer Complaints, identifying low Customer Satisfaction. This issue arise due to long delivery lead times and low quality of delivered materials. Currently, Customer Support is running around US 20 million business per year, and targeted by the Board to achieve US 100 million in the coming years. In order to change this situation, we identify the issue by using DMAIC method, and improvement shall be made, especially for the Purchasing Strategy, where it is one of the root cause indicating the low performance of Procurement in terms of supporting Customer Support.